(untitled) (Global Journal of Human-Social Science, 2024)
The view that a text is an autonomous hermetic self-contained system is a myth Every text is constituted by a mosaic of citations every text is the absorption and transformation of another text Kristeva 1986 37 Our purpose in this article is to show that there is an intertextual relation between the later poetry of KPD Maphalla and the earlier poems of KE Ntsane BM Khaketla and MA Mokhomo that a text has the meaning it does only because certain things were written before This calls our attention to the importance of prior texts and how they relate to later texts Hillis Miller 1979 225 writing about the symbol of host and parasite in literature says later texts contain long chains of parasitical presences This view of intertextual relations suggests that there is cannibalism between texts where the later work simply feeds on the earlier work without shame On the contrary the analytical approach we adopt in this paper derives from the theory of intertextuality as initiated and developed by Julia Kristeva 1966 1967 1980 1986 together with the Tel Quel group Here intertextuality is viewed as a dynamic site where earlier and later texts intersect enter a dialogue negotiate a plurality of meaning and enrich one another